Market Classifications in Modern Price Theory - Bain, Joe S. (Quarterly Journal of Economics, 1942)
Three elements in price theory, 560. — Shortcomings of contemporary price theory: the Robinsonian theory, 562; the Chamberlinian theory, 565. — Neglected market characteristics, 568. — Suggested classification of markets, 569. — Comment on such classifications, 572. — Suggested lines of development, 574.